2020
DOI: 10.1155/2020/8605485
|View full text |Cite
|
Sign up to set email alerts
|

Haematological and Biochemical Reference Values for Healthy Population of Maferinyah Rural Community in Guinea

Abstract: Guinea’s reference ranges for biological parameters rely on those of Caucasian values. Variability in reference ranges according to the context is well-documented. We conducted this study for the purpose of future malaria clinical trials that assess the efficacy and safety of malaria drugs. A repeated cross-sectional study was carried out, in an apparently healthy cohort population. Surveys took place in Maferinyah rural community, which is located at 75 km from the capital. The 2.5th and 97.5th percentiles we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 32 publications
3
2
1
Order By: Relevance
“…several studies revealed significant differences in hematology reference range amongst children of different ages, as well as in populations, seasons, racialethnic groups, and gender subgroups. (Sahoo et al,2015, Béavogui et al 2020. Current findings revealed that the mean of Hb concentration regarding different age groups ( 3-7, 8-12, 13-17) is (12.4, 12, 12.5, 12.4) respectively, this agrees with Al-Jafars' study (Al-Jafar, 2016).…”
Section: Sample Collectionsupporting
confidence: 85%
“…several studies revealed significant differences in hematology reference range amongst children of different ages, as well as in populations, seasons, racialethnic groups, and gender subgroups. (Sahoo et al,2015, Béavogui et al 2020. Current findings revealed that the mean of Hb concentration regarding different age groups ( 3-7, 8-12, 13-17) is (12.4, 12, 12.5, 12.4) respectively, this agrees with Al-Jafars' study (Al-Jafar, 2016).…”
Section: Sample Collectionsupporting
confidence: 85%
“…To discourage this trend, this study is aimed at creating a local standard for interpreting medical laboratory findings by determining the CBC reference intervals for children aged less than 1-12 years in Tamale, Northern Ghana. This study observed no significant differences in most CBC reference intervals when compared by sex and age group, except for Hb, MCV, MCH, MCHC, PLT, and absolute basophils, similar to studies in Guinea [21] and China [22], but contrary to a study in Macedonia [23], which showed a steady increase in CBC reference intervals with age. The inability of this study to detect and exclude children who may present with mild anaemia due to thalassaemia, evaluate their nutritional status to rule out conditions such as subclinical iron deficiency anaemia, and instead rely solely on subjective health and the absence of persistent or recent diseases may account for this difference in outcomes [21,22,24].…”
Section: Percentagesupporting
confidence: 78%
“…This study observed no significant differences in most CBC reference intervals when compared by sex and age group, except for Hb, MCV, MCH, MCHC, PLT, and absolute basophils, similar to studies in Guinea [21] and China [22], but contrary to a study in Macedonia [23], which showed a steady increase in CBC reference intervals with age. The inability of this study to detect and exclude children who may present with mild anaemia due to thalassaemia, evaluate their nutritional status to rule out conditions such as subclinical iron deficiency anaemia, and instead rely solely on subjective health and the absence of persistent or recent diseases may account for this difference in outcomes [21,22,24]. This was confirmed by the statistically significant differences in Hb, MCV, MCH, and MCHC by sex and age group observed in this study [23,25].…”
Section: Percentagesupporting
confidence: 78%
“…Because PV changes are not considered in the [Hb] thresholds established by the WHO to diagnose anemia, this diagnostic model presents substantial limitations (16,17). Numerous studies have soundly measured reference hematological values, including [Hb], in populations with high anemia prevalence according to the WHO website, notably in women of reproductive age and young children (< 5 years old) (39)(40)(41)(42)(43)(44)(45)(46). Such countries are described with a severe anemia prevalence by the WHO with values going from 40% to 69% in either populations (12,47).…”
Section: Discussionmentioning
confidence: 99%